The neural circuits and molecular mechanisms underlying fear dysregulation in posttraumatic stress disorder - Iqbal, Javed; Huang, Geng-Di; Xue, Yan-Xue; Yang, Mei; Jia, Xiao-Jian (Frontiers in Neuroscience, 2023)
Post-traumatic stress disorder (PTSD) is a stress-associated complex and debilitating psychiatric disorder due to an imbalance of neurotransmitters in response to traumatic events or fear. PTSD is characterized by re-experiencing, avoidance behavior, hyperarousal, negative emotions, insomnia, personality changes, and memory problems following exposure to severe trauma.However, the biological mechanisms and symptomatology underlying this disorder are still largely unknown or poorly understood. Considerable evidence shows that PTSD results from a dysfunction in highly conserved brain systems involved in regulating stress, anxiety, fear, and reward circuitry. This review provides a contemporary update about PTSD, including new data from the clinical and preclinical literature on stress, PTSD, and fear memory consolidation and extinction processes. First, we present an overview of well-established laboratory models of PTSD and discuss their clinical translational value for finding various treatments for PTSD. We then highlight the research progress on the neural circuits of fear and extinction-related behavior, including the prefrontal cortex, hippocampus, and amygdala. We further describe different molecular mechanisms, including GABAergic, glutamatergic, cholinergic, and neurotropic signaling, responsible for the structural and functional changes during fear acquisition and fear extinction processes in PTSD.